اسرتاتيجيات تطوير االوقاف يف سنغافورة - mohamed, ASHRAF JOMAH MOHAMMED; Saleh, Abdulmajid Obaid Hasan; Mohd Noor, Azman (AlHikmah Research and Publication Centre, 2019)
Many Waqf institutions face difficulties in financing Waqf projects, developing them and transforming them into productive endowments, with higher and more efficient revenues in their developmental contribution. Endowments in Singapore are models that guide the endowments produced efficiently and effectively, and contribute significantly to economic and social development. Some models applied by the Islamic Council of Singapore to finance Waqf assets development projects through (Wares) to develop Waqf assets, turn them into self-financed endowments, and contribute effectively to the development of the Muslim community in Singapore. The researcher used the inductive method by reviewing the published articles, books and reports on the experience of Singapore in financing endowment development projects. The most important conclusion of the paper is that the productive management of endowments has contributed significantly to the development of endowments in Singapore. Assets and increased Muslim pride in the ability of the Islamic Council to excel and perform effectively -------------------------------------- تواجه الكثري من املؤسسات الوقفية صعوابت يف إدارة األراضي الوقفية وتطو يرها وحتويلها الوقاف منتجة،ذات ايراد عاىل واكثر فاعلية يف املسامهتها التنميوية، وقدمت االوقاف يف سنغافورة منوذج يهتدى به يف تنمية وتطوير االوقاف بشكل عام واالراضي الوقفية بشكل خاص، و هتدف هذه الورقة إىل استغراض بعض النماذج اليت طبقها اجمللس االسالمي يف سنغافورة يف تطوير بعض االصول الوقفية من خالل شركة (wares )ويرس لتطوير وجتدبد االصول الوقفية، وحتو يلها الوقاف ذاتية التمويل وتسهم بفاعلية يف تنمية اجملتمع املسلم يف سنعافورة، و استخدم الباحث املنهج االستقرائي من خالل مراجعة ما نشر من مقاالت و كتب وتقارير حول جتربة سنغافورة يف تطوير األصول الوقفية، واهم ما خلصت اليه الو رقة أن االدارة االنتاجية لالوقاف سامهة بشكل كبري يف تنمية وتطوير االوقاف يف سنغافور ة، ودل على هذا النجاح الزايدة يف قيمة وايرادات هذة االصول وزايدة ثفة املسلمني يف قدرته على التميز واالداء الفعال.